Nissen-Sleeve procedure versus laparoscopic Roux-en-Y gastric bypass in patients with morbid obesity and gastro-oesophageal reflux disease: protocol for a non-inferiority randomised trial (GINSBY) - Jan A Apers; Martin Dunkelgrun; Ivonne Leeuwenburgh; Judith W H 't Hart; Bo J Noordman; Laser U Biter (BMJ Open)
Introduction Laparoscopic sleeve gastrectomy (LSG) and laparoscopic Roux-en-Y gastric bypass (LRYGB) are the most frequently performed procedures in bariatric surgery. In patients with morbid obesity and gastro-oesophageal reflux disease (GORD), LRYGB is the most accepted procedure. For patients with a contraindication for LRYGB or a strong preference for LSG, the Nissen-Sleeve procedure may be a viable new option. The aim of this study is to compare effectiveness of Nissen-Sleeve with LRYGB.Method and analysis This is a single-centre, phase III, parallel-group randomised controlled trial in a high-volume bariatric centre in the Netherlands. A total of 88 patients with morbid obesity and GORD will be randomised to evaluate non-inferiority of Nissen-Sleeve versus LRYGB (non-inferiority margin 15%, power 80%, one-sided α 0.025, 9% drop out). Patients with morbid obesity aged 18 years and older with GORD according to the Montreal definition will be included after obtaining informed consent. Exclusion criteria are achalasia, neoplastic abnormalities diagnosed during endoscopy, super obesity (body mass index ≥50 kg/m2), Crohn’s disease and medical history of major abdominal surgery. After randomisation, all patients will undergo an upper gastrointestinal endoscopy. Patients in the Nissen-Sleeve arm will undergo a timed barium oesophagram to exclude oesophageal motility disorders. Patients will complete six questionnaires at baseline and every year until 5 years of follow-up. At day 1 postoperative, patients in the Nissen-Sleeve arm will undergo a swallow X-ray to confirm passage. At 1 year, all patients will undergo another endoscopy. The primary outcome is GORD status. Absence of GORD is defined as <8 points on the GORD questionnaire. Secondary outcome measures are long-term GORD improvement; failure rate of procedure; health-related quality of live; weight loss; proton pump inhibitor use; postoperative complications <30 days and >30 days; length of hospital stay; duration of primary surgery; effect on comorbidities; presence and grade of oesophagitis (grade A–D) and/or presence of Barrett’s oesophagus and cost-effectiveness.Ethics and dissemination The protocol was approved by the Medical Research Ethics Committees United (MEC-U), Nieuwegein, on 15 September 2021. Written informed consent will be obtained for all participants in the study. The study results will be disseminated through peer-reviewed publications and conference presentations.Trial registration number NL9789; The Netherlands Trial Registry.